(4z-10)+1z=90

Simple and best practice solution for (4z-10)+1z=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4z-10)+1z=90 equation:


Simplifying
(4z + -10) + 1z = 90

Reorder the terms:
(-10 + 4z) + 1z = 90

Remove parenthesis around (-10 + 4z)
-10 + 4z + 1z = 90

Combine like terms: 4z + 1z = 5z
-10 + 5z = 90

Solving
-10 + 5z = 90

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 5z = 90 + 10

Combine like terms: -10 + 10 = 0
0 + 5z = 90 + 10
5z = 90 + 10

Combine like terms: 90 + 10 = 100
5z = 100

Divide each side by '5'.
z = 20

Simplifying
z = 20

See similar equations:

| (6x+10)/11=-4 | | 7/(4x-1)=2/(x+5) | | -6/5(-4)+31/5 | | 15=6a-24-9a | | 7-3x=1/4(8x-12) | | 2T=T-(84*.5) | | 6x^7/5-66=0 | | 9xy^2*9x^5y^2= | | 6m+9(2-m)=2(7-4m)-11 | | 15(x^2+2x)= | | 1+999= | | 3+6(7n+3)=-147 | | 4(9-3)/(8-2) | | 18(-y-2)-4(-9+3y)+76=-14 | | 9x+4+3x=7x+x+14 | | -3/4(-x-8)=x+10 | | y=8+2z | | -4/5(z+3)=-2/3(z-4/5) | | a=(w)(3w) | | 3y+2-4y=9 | | 2/3/1/8 | | x^2-23x+26=0 | | 1.06g-3=0.7 | | -132=-4a-8(-4a+6) | | 3(x-5)=2(x+6) | | -35+7m= | | -5(r+7)=-63 | | -18x^2+23x+6=0 | | -2[8-(4-w)]-8=4(w+5) | | f(3)=3x^2+7 | | (y-5)-2=10 | | .4x-3+2x=4-6-2x |

Equations solver categories